Kemampuan dalam Menulis Berita Bahasa Jawa Menggunakan Metode Project Based Learning pada Siswa Kelas VIII MTs Al-Ma’arif Gembong - Sukmayani, Bella Aidha; Zaidah, Nuning; Sunarya, Sunarya (Universitas PGRI Semarang, 2025)
This study aims to describe the results of the ability to write Javanese language news using the Project Based Learning method in class VIII students of MTs AL-M'ARIF Gembong Pati. This is due to the lack of interest of students in learning to write Javanese language news and the learning method is less appropriate so that there is a lack of enthusiasm in the learning process in the classroom. Thus, the formulation of the problem in this study is how are the results of the ability to write Javanese language news using the Project Based Learning method. This study is included in pre-experimental research, namely one-shot case study. The approach used in this study is a descriptive quantitative approach, the calculation of data used in the study in the form of purposive sampling, and the data obtained in this study were collected by taking documentation and questionnaires. From the percentage, it can be concluded that the category of student scores in the knowledge aspect is fairly good according to the assessment guidelines, namely with an average score of 83.78. 2) In the skills aspect, there are 11 students with a percentage of 37% in the very good category. In addition, there are 17 students with a percentage of 57% in the good category. Then as many as 2 students with a percentage of 7% with a sufficient category. From this percentage it can be concluded that the category of student scores is fairly good according to the assessment guidelines, which is an average of 84.97. Thus, the ability to write Javanese language news using the Project Based Learning method in class VIII students of MTs AL-MA'ARIF Gembong Pati can have an influence on learning achievement.